Implementasi Program Literasi Al-Qur’an sebagai Strategi Pembentukan Karakter pada Siswa MTs. Zia Salsabila Deli Serdang - Sartika Sari Efriyanti; Hasan Asari (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyse the implementation of the Quranic literacy program as a strategy for character building for students at MTs Zia Salsabila, covering aspects of planning, implementation, and evaluation. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation, then analysed using the Miles and Huberman model, which includes data reduction, data presentation, and concluding. The results of the study indicate that the Quranic literacy program was planned systematically and sustainably to improve students' ability to read the Quran and shape their religious character. It is implemented routinely every morning through structured activities involving students and teachers as supervisors. Evaluation shows that approximately 70% of students have achieved the target, although some students still struggle to perform optimally. Overall, the Quranic literacy program makes a positive contribution to the formation of student character, especially in aspects of discipline, responsibility, and religiosity. In addition to improving the ability to read the Quran, this program also builds a school culture conducive to strengthening spiritual values, developing disciplined learning habits, and complying with madrasah regulations. The involvement of all teachers in the supervision process demonstrates institutional collaboration that supports the program's success. Research findings also indicate that successful character building is determined not only by routine activities but also by the management system, regular evaluations, and parental support in guiding students at home. Therefore, the Quranic literacy program can be positioned as a relevant and sustainable character education strategy to address the challenges of adolescent moral development in the digital age.